Toxicity Assessment of Molybdenum Nanooxide in Relation to Various Components of the Agroecosystem in a Model Experiment - Lyudmila Galaktionova; Irina Vershinina; Svyatoslav Lebedev (Soil Systems)
(1) Background: The rapid growth in the number of nanoparticles today raises questions about studying their impact on the environment, including the soil, as the main absorber of nanoparticles. The purpose of our research was to study the effect of MoO3 nanoparticles (NPs; 50, 100, 250, 500, and 1000 mg/kg of soil) on the physiological and biochemical parameters of Eisenia fetida, the number of certain ecologo-trophic groups of soil microorganisms, and enzymatic soil activity. (2) Methods: We used 92 ± 0.3 nm nanoparticles of MoO3 at concentrations of 50, 100, 250, 500, and 1000 mg/kg dry soil. Texture-carbonate chernozem was used in the study. Eisenia fetida worms were used as test objects. (3) Results: The introduction of MoO3 nanoparticles showed a weak toxic effect towards the animal and microbiological components of the soil at a concentration of 50–250 mg/kg, a medium toxic effect at 500 mg/kg, and a strong or unacceptable toxic effect at 1000 mg/kg. The oxidative stress response of E. fetida depended on the concentration of the NPs. MoO3 NPs at a concentration of up to 100 mg/kg reduced the number of amylolytic bacteria, oligotrophs, and Azotobacter. In soil, urease and catalase showed mild activity, whereas the activity of invertase decreased by 34%. (4) Conclusions: The entry into the environment and the further deposition of nanoparticles of Mo and its oxides in the soil will lead to the suppression of the vital activity of beneficiary soil animals and the activity of soil enzymes. This phenomenon presents special kinds of ecological risks for the ecosystem.